3D guidance for hypersonic reentry gliders based on analytical prediction. (February 2020) - Pan, Liang; Peng, Shuangchun; Xie, Yu; Liu, Yang; Wang, Jianhong
Abstract: In order to give full play to the potential of hypersonic gliders to strike a longrange of targets and perform large lateral maneuvering missions, a three-dimensional guidance method is proposed on the basis of analytical predictions. We first construct an entry guidance model for a glider and derive the analytical solution for the trajectory based on Lyapunov's artificial small parameter method. Such an approach ensures high accuracy in the theoretical prediction of flight trajectory. Subsequently, we construct a three-dimensional (3D) flight corridor that satisfies multiple constraints including heat rate, dynamic pressure, overload, angle of attack, and bank angle. Furthermore, the flight profile and bank reversal strategy in the 3D flight corridor model are designed on the basis of the analytical solution of the flight trajectory considering both longitudinal flight range and lateral flight mobility requirements of the glider. In addition, the control commands of the angle of attack and bank angle are generated by tracking the profile of the flight. The method has been tested in three cases of guidance under short-, medium-, and long-range flights. The results show that it provides high prediction accuracy and strong self-adaptive capability for all the test cases. Our proposed method targets the design of a 3D flight profile in a 3D flight corridor. Furthermore, the method considers flight requirements in both the longitudinal and lateral directions, thus maximising the aircraft's ability to reach the target while maintaining high levels of flexibility and self-adaptive capability during the mission. Highlights: A three-dimensional guidance method is proposed on the basis of analytical predictions. Our proposed method targets the design of a 3D flight profile in a 3D flight corridor. The method has been tested in three cases of guidance under short-, medium-, and long-range flights. The method can make the most of aircraft's ability to reach the target.